Ultrahigh cryogenic strength and exceptional ductility at 20 K in a TWIP Ti–15Mo alloy. (May 2022) - Yao, Kai; Xin, Shewei; Yang, Yi; Du, Yu; Dai, Jincai; Li, Ting; Min, Xiaohua
Abstract: The tensile behavior of metastable β-type Ti-15Mo alloy for cryogenic applications with {332}<113> twinning-induced plasticity (TWIP) effect was examined at 20 K. An ultrahigh strength of 1725 MPa with an excellent elongation of 10% was found, which constitutes a major advance in the field of titanium alloys for cryogenic applications. A distinctly serrated tensile curve and multiple necking were detected, and their correlations were revealed to be based on the formation of twins. The local plastic deformation and necking were hindered by abundant {332}<113> twins and piled-up dislocations at twin boundaries, resulting in a simultaneous enhancement of the strength and ductility. Exploiting the {332}<113> TWIP effect in body-centered cubic (BCC) structured titanium alloys constitutes a novel strategy for the development of cryogenic alloys. Graphical abstract: Image, graphical abstract